2018
DOI: 10.1021/acsearthspacechem.7b00120
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organic Aerosol in Atmospheric Ice Nucleation: A Review

Abstract: Predicting the formation of ice in the atmosphere presents one of the great challenges in 14 physical sciences with important implications for the chemistry and composition of the Earth's atmos-15 phere, the hydrological cycle, and climate. Among atmospheric ice formation processes, heterogeneous 16 ice nucleation proceeds on aerosol particles ranging from a few nanometers to micrometers in size, 17 commonly referred to as ice nucleating particles (INPs). Research over the last two decades has demon-18 strated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
442
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(450 citation statements)
references
References 473 publications
8
442
0
Order By: Relevance
“…The C-rich particles encountered are most likely organic aerosol. This is in good accordance with the results of many field studies (see the recent review by Knopf et al (2018) and references therein) which show that organic aerosol is found in the IPR fraction, but is depleted relative to total aerosol.…”
supporting
confidence: 92%
“…The C-rich particles encountered are most likely organic aerosol. This is in good accordance with the results of many field studies (see the recent review by Knopf et al (2018) and references therein) which show that organic aerosol is found in the IPR fraction, but is depleted relative to total aerosol.…”
supporting
confidence: 92%
“…Molecular motion can be hindered in a highly viscous matrix, slowing down photochemical reactions in particles (Lignell et al, 2014;Hinks et al, 2016). Water diffusion can still be fast even in an amorphous solid matrix under room temperature, but it can be hindered significantly under low temperatures (Mikhailov et al, 2009;Zobrist et al, 2011;Bones et al, 2012;Berkemeier et al, 2014;Price et al, 2014), affecting homogeneous vs. heterogeneous ice nucleation pathways (Murray et al, 2010;Wagner et al, 2012;Wang et al, 2012a, b;Wilson et al, 2012;Baustian et al, 2013;Schill and Tolbert, 2013;Schill et al, 2014;Lienhard et al, 2015;Ignatius et al, 2016;Knopf et al, 2018). Despite the substantial implications of the SOA particle phase state, its effects on gasparticle interactions have not yet been considered explicitly in current climate and air quality models (Shrivastava et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…after cloud processing, where the aerosol first activated to supercooled cloud droplets and then froze homogeneously (Ladino et al, 2014;Wagner et al, 2017). These and other studies on the ice-nucleating ability of SOA particles are summarized in Hoose and Möhler (2012) and Knopf et al (2018). It has to be stressed that in the above-mentioned studies and our study the SOA generation procedures and conditions can vary significantly, as can the methods used to measure ice nucleation; see the Introduction for details.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, an effect of different temperatures in the chambers or sampling lines was found and discussed by e.g. Ignatius et al (2016) and Knopf et al (2018). However, the aerosol chamber DMPS and cloud chamber SMPS aerosol size distributions do not indicate major growth of particles between transfer and cloud evacuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation